Efficient ℓq regularisation algorithm with range–azimuth decoupled for SAR imaging. Issue 3 (1st January 2014) - Jiang, C.L.; Zhang, B.C.; Fang, J.; Zhe, Z.; Hong, W.; Wu, Y.R.; Xu, Z.B.
Abstract : The synthetic aperture radar (SAR) imaging methods based on compressive sensing endure great computational complexity since they have to deal with a large measurement matrix when processing the raw data. An efficient ℓ q regularisation algorithm for SAR imaging is proposed, which uses a decoupling operator constructed by means of chirp scaling. It can reduce the computational complexity from the square order to the linear logarithm order compared with the conventional ℓ q regularisation‐based imaging algorithm while preserving the equivalent imaging quality. The proposed algorithm is efficient in the sense that it allows reconstruction of the sparse scenes with the sub‐sampling data.